Cost-effectiveness of silver dressings for paediatric partial thickness burns: An economic evaluation from a randomized controlled trial. Issue 4 (June 2017) - Gee Kee, E.; Stockton, K.; Kimble, R.M.; Cuttle, L.; McPhail, S.M.
Highlights: Economic evaluation comparing silver dressings for paediatric partial thickness burns. 96 children in the trial investigating Acticoat™, Acticoat™ with Mepitel™ or Mepilex Ag™. Mepilex Ag™ costs were considerably lower than Acticoat™ and Acticoat™ with Mepitel™. There was a 99% and 97% probability Mepilex Ag™ dominated Acticoat™ and Acticoat™ with Mepitel™. Abstract: Background: Partial thickness burns of up to 10% total body surface area (TBSA) in children are common injuries primarily treated in the outpatient setting using expensive silver-containing dressings. However, economic evaluations in the paediatric burns population are lacking to assist healthcare providers when choosing which dressing to use. The aim of this study was to conduct a cost-effectiveness analysis of three silver dressings for partial thickness burns ≤10% TBSA in children aged 0–15 years using days to full wound re-epithelialization as the health outcome. Method: This study was a trial based economic evaluation (incremental cost effectiveness) conducted from a healthcare provider perspective. Ninety-six children participated in the trial investigating Acticoat™, Acticoat™ with Mepitel™ or Mepilex Ag™. Costs directly related to the management of partial thickness burns ≤10% TBSA were collected during the trial from March 2013 to July 2014 and for a one year after re-epithelialization time horizon. Incremental cost effectiveness ratios were estimated and dominance probabilities calculated from bootstrap resampling trial data. Sensitivity analyses were conducted to examine the potential effect of accounting for infrequent, but high cost, skin grafting surgical procedures. Results: Costs (dressing, labour, analgesics, scar management) were considerably lower in the Mepilex Ag™ group (median AUD$94.45) compared to the Acticoat™ (median $244.90) and Acticoat™ with Mepitel™ (median $196.66) interventions. There was a 99% and 97% probability that Mepilex Ag™ dominated (cheaper and more effective than) Acticoat™ and Acticoat™ with Mepitel™, respectively. This pattern of dominance was consistent across raw cost and effects, after a priori adjustments, and sensitivity analyses. There was an 82% probability that Acticoat™ with Mepitel dominated Acticoat™ in the primary analysis, although this probability was sensitive to the effect of skin graft procedures. Conclusion: This economic evaluation has demonstrated that Mepilex Ag™ was the dominant dressing choice over both Acticoat™ and Acticoat™ with Mepitel™ in this trial-based economic evaluation and is recommended for treatment of paediatric partial thickness burns ≤10% TBSA.